2019
DOI: 10.1186/s12955-019-1181-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of missing data on bias and precision when estimating change in patient-reported outcomes from a clinical registry

Abstract: Background Clinical registries, which capture information about the health and healthcare use of patients with a health condition or treatment, often contain patient-reported outcomes (PROs) that provide insights about the patient’s perspectives on their health. Missing data can affect the value of PRO data for healthcare decision-making. We compared the precision and bias of several missing data methods when estimating longitudinal change in PRO scores. Methods This re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(63 citation statements)
references
References 35 publications
0
63
0
Order By: Relevance
“…Another limitation is that there were some randomly distributed missing data. This can lead to bias and reduced precision when analyzing patientreported outcomes (37). Surveys are prone to having missing data although in this case, the number of missing values was low.…”
Section: Strengths Limitations and Next Stepsmentioning
confidence: 99%
“…Another limitation is that there were some randomly distributed missing data. This can lead to bias and reduced precision when analyzing patientreported outcomes (37). Surveys are prone to having missing data although in this case, the number of missing values was low.…”
Section: Strengths Limitations and Next Stepsmentioning
confidence: 99%
“…Missing data can occur for various reasons during the data collection process, such as incomplete responses (Pampaka et al, 2016;Barnett et al, 2017), equipment malfunction (Masconi et al, 2015;Gopal et al, 2019) and manual data entry errors (Bhati & Gupta, 2016). Incomplete data is a serious data quality problem since it leads to a reduction of statistical power, bias in parameter estimates, and loss of efficiency in the analytical process (Kaiser, 2014;Ayilara et al, 2019;Hughes et al, 2019). These problems have led to extensive research on developing methods to treat missing data.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis models would be the same as other statistical model with complete data sets. Many studies indicated that the imputation model should contain all variables in the analysis model or any auxiliary variables relating with outcome variables likely to be used in the subsequent analyses [19,23]. For each of 30 simulation data sets and the data set K, taking Y 1 as the dependent variable and the others as the covariates for regression analysis.…”
Section: Analysis Modelsmentioning
confidence: 99%
“…For MI, it can provide unbiased estimates of the regression parameter of interest when the missing data is MAR or MCAR. Recent study found when the missing data is assumed to be MAR or MCAR, CCA was performed well (e.g., unbiased risk difference, 95% coverage) [5], although some papers indicated that the method can result in substantially bias [3,9,19]. The application of SI is the same as CCA and MI, for example, inverse probability weighting (IPW) is typically implemented assuming MAR [20][21].…”
Section: Introductionmentioning
confidence: 99%